Lipophilic polymethacrylate ionic liquids as lubricant additives. (November 2018) - Bapat, Abhijeet P.; Erck, Robert; Seymour, Bryan T.; Zhao, Bin; Cosimbescu, Lelia
Graphical abstract: Highlights: Lipophilic polymethacrylate ionic liquids were prepared via scalable methods. They were evaluated for viscosity index, friction, and wear. All analogs displayed a competitive viscosity index, ∼200 or higher. Polymers bearing a dicyanamide anion showed 90% lower wear than benchmarks. Abstract: Despite the growing research field of polymeric ionic liquids used as materials for electrolytes and energy materials, catalysts, separation aides, and carbon materials, reports of lipophilic polymeric ionic liquids for lubricants are essentially nonexistent. Oil-miscible single molecule ionic liquids (ILs) are reported to perform well as neat lubricants and as additives in lubricating base oils. In this work, methacrylate type ionic liquid monomers containing ammonium or imidazolium cations and two different counter-anions were synthesized and used as co-monomers to obtain functional poly(alkyl methacrylates) (PAMAs) as viscosity index improvers (VII) additives for lubricants. The structure of the IL, including the cation, the anion, and the spacer's length separating the IL from the methacrylate group, plays an important role in the resulting polymer solubility in PAO (poly-alpha olefin), solution rheology, friction, and wear behavior. Depending on the IL structure, VIIs containing up to 20% mol IL are soluble in PAO (grade 4), and demonstrate frictionandwear reduction, compared to a conventional oil-soluble PAMA. Notably, wear volume reduction of up to 80% compared to the oil-soluble control poly(dodecyl methacrylate) is observed.